Late Roman (late 4th to 7th century) Ceramics from the Panayia Field in Corinth, Greece: The Local and Regional Networks of a Globalized City - Hammond, Mark D. (Rei Cretariae Romanae Fautorum Acta, 2022)
Corinth’s position along the empire-wide distribution networks of the Late Roman world allowed it to receive a variety of ceramics imported from long-distance centres, but the city was also supplied by numerous regional (Attic, Boiotian, and southern Argolid) and local sources. Extensive typological and fabric analyses of the ceramic material recovered from the excavations of the Panayia Field in Corinth have provided the opportunity to identify and characterize all of the major local and regional wares supplying the site. While the production and distribution patterns of each naturally evolved and shifted over time, changes at local and regional levels had the potential to affect Corinth’s interaction with long distance networks. Likewise, changes in empire-wide patterns could also affect the city’s interactions with neighboring regions. The material from the Panayia Field illustrates that the impact of local and regional centres of ceramic production was not geographically limited, but could in fact interact with, influence, and be affected by long distance networks and trends.